The foresight principle in government - Solem, Knut Erik (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
This article examines the role of foresight in government and explains why it is both necessary and rare. It outlines the characteristics of foresight, its main methods and techniques with particular reference to holistic models and their use. The article identifies areas where foresight is needed as well as the types of constraints it faces. The relationship between foresight and planning is discussed, and some prescriptions and recommendations are offered.
Keywords: vladanje; odločanje; sprejemanje odločitev; predvidevanje; postopki; modeli